2018
DOI: 10.1159/000491999
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sunitinib in Patients with Well-Differentiated Pancreatic Neuroendocrine Tumours

Abstract: Background: In a phase III study, sunitinib led to a significant increase in progression-free survival (PFS) versus placebo in patients with pancreatic neuroendocrine tumours (panNETs). This study was a post-marketing commitment to support the phase III data. Methods: In this ongoing, open-label, phase IV trial (NCT01525550), patients with progressive, advanced unresectable/metastatic, well-differentiated panNETs received continuous sunitinib 37.5 mg once daily. Eligibility criteria were similar to those of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 18 publications
4
54
0
2
Order By: Relevance
“…The results of this PMS study showed the safety profile of sunitinib in Japanese patients with pNETs treated in clinical practice was similar to the safety profile in patients treated in clinical trials, including the global phase III and IV trials and the phase II trial in Japanese patients [ 8 , 11 , 19 ]. Furthermore, there were no new safety concerns in sunitinib-treated Japanese patients with pNETs, and the commonly reported AEs were similar to those previously reported in clinical trials and surveillance studies of sunitinib in patients with metastatic renal cell carcinoma and gastrointestinal stromal tumors [ 20 24 ].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The results of this PMS study showed the safety profile of sunitinib in Japanese patients with pNETs treated in clinical practice was similar to the safety profile in patients treated in clinical trials, including the global phase III and IV trials and the phase II trial in Japanese patients [ 8 , 11 , 19 ]. Furthermore, there were no new safety concerns in sunitinib-treated Japanese patients with pNETs, and the commonly reported AEs were similar to those previously reported in clinical trials and surveillance studies of sunitinib in patients with metastatic renal cell carcinoma and gastrointestinal stromal tumors [ 20 24 ].…”
Section: Discussionmentioning
confidence: 57%
“…In fact, the median duration of treatment in this PMS study was shorter than in the global phase IV trial (356 days) or the real-world clinical setting of the Japanese clinical study (490 days) [ 19 , 25 ]. The longer treatment duration in those trials likely led to the better outcomes: ORR was 24.5% in the global phase IV trial and 44% in the Japanese study [ 19 , 25 ]. Keeping patients on treatment longer, by appropriately managing AEs at early stages, is essential for achieving better clinical outcome in sunitinib-treated patients with pNETs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В 2018 г. Raymond и соавт. [6,7] подтвердили результаты 3 фазы в исследовании 4 фазы у пациентов с прогрессирующими неоперабельными НЭО ПЖ G1-2. Медиана ВБП у пациентов, получавших сунитиниб в дозе 37,5 мг в день ежедневно, составила 13,2 месяца, а частота объективных ответов -24,5%.…”
Section: Clinical Observationunclassified
“…В дальнейшем Raymond и соавт. [6,7] провели исследование 4-й фазы (NCT01525550) при прогрессирующих, высокодифференцированных, неоперабельных или диссеминированных НЭО ПЖ. Пациенты также получали сунитиниб в дозе 37,5 мг в день ежедневно.…”
Section: Introductionunclassified